Woman, culture and society - Rosaldo, Michelle Zimbalist; Lamphere, Louise (Stanford Stanford University Press, 1974)
Sixteen women anthropologists analyze the place of women in human societies, treating as problematic certain questions and observations that in the past have been ignored or taken for granted, and consulting the anthropological record for data and theoretical perspectives that will help us to understand and change the quality of women's lives.
Keywords: Woman-Culture; Society; Women anthropologists